Their monstrous hearts - Turhan, Yiğit (Mira, 2025)
"A mysterious stranger shows up at Riccardo's apartment with some news: his grandmother Perihan has died, and Riccardo has inherited her villa in Milan along with her famed butterfly collection. The struggling writer is out of options. He's hoping the change of scenery in Milan will inspire him, and maybe there will be some money to keep him afloat. But Perihan's house isn't as opulent as he remembers. The butterflies pinned in their glass cases seem more ominous than artful. Perihan's group of mysterious old friends is constantly lurking. And there's something wrong in the greenhouse"--